Sweet Potato Seed Systems and Crop Management Community of Practice. - McEwan, M. (2018)
The Sweetpotato Seed Systems and Crop Management Community of Practice (SS-CoP) Eighth Consultation was held from 21-22 November 2017 at Pride Inn, Nairobi, Kenya. The planning and review meeting was attended by the Sweetpotato Action for Security and Health in Africa (SASHA) project pre-basic seed (PBS) system sub-grantees. There were 24 participants from 11 countries - Ethiopia, Kenya, Uganda, Tanzania, Ghana, Nigeria, Burkina Faso, Malawi, Mozambique, Nigeria and Zambia. The participants were predominantly sweetpotato breeders, and seed systems scientists implementing business plans for sustainable production of sweetpotato seed. Each country made presentations of their activities for the period of June-November 2017, with a focus on production capacities, production targets vs. actual achievements and comments on how to improve multiplication rates and reduce production costs; quality management; estimated pre-basic seed requirements for the coming season; progress in implementing their business plans and revolving funds and capacity building initiatives undertaken. In discussion groups, they deliberated on their successes, lessons and the improvements they needed to make to improve the sustainability of their pre-basic seed production and marketing. Prior to the main meeting, the CIP team and principal investigator (PI) worked together to review the progress report and the completion of the business plan financial analysis.